Effect of aluminum chloride against changes of the histological structure of the cerebral cortex of mice (swiss webster) - Yulia Irnidayanti; Risa Eno Aprilyanti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
The toxicity of metal to living organisms, including human beings, was discovered a long time ago. In the present time, aluminum exposure is widely used for wrapping food to keep it taste and smell. However it will affect to human health security, specially the brain. This study aimed to investigate the changes of histological Structure on the cerebral cortex caused by aluminum chloride. The mice were injected intraperitoneally with AlCl3 200 mg/kg body weight, once every 3 days, totalizing 10 administrations. Control only was administration distilled water. Histological observations were carried out using the paraffin method. The results of this study show that aluminum chloride cause disorganization of the laminated cerebral cortex, vacuolization, karyolysis, congestion, and hemorrhage. The mice of one and two-months of age group were more susceptible to aluminum chloride than the mice of the three-months of age group. This research can apply for an assessment of the exposure risk to heavy metal. Increasing Al contamination can occur naturally or by anthropogenic activities. The accumulation of the heavy metal in the organism can occur by biomagnification, by which heavy metal is passed from one trophic level to the next within a food web. Therefore communities that live in urban areas potentially exposed to metals aluminum and should be more concerned related to understanding health risks. Further studies are needed to examine the above matters. We recommend calculating the Provisional Tolerable Weekly Intake of aluminum and implication on local people